State of the Art of Triad-Based Ecological Risk Assessment: Current Limitations and Needed Implementations in the Case of Soil Diffuse Contamination - Grassi, Giacomo; Lamy, Isabelle; Pucheux, Nicolas; Ferrari, Benoit Jean Dominique; Faburé, Juliette (Frontiers in Environmental Science, 2022)
Soils can be the sink of pollutant mixtures, whose effects on terrestrial ecosystems are not yet of obvious interpretation. Risk assessment is rather codified and many approaches can be used. Nevertheless, there are still questions remaining when dealing with diffuse pollution, including chronic inputs of low, subletal, concentrations of mixtures of micropollutants. In this paper, we reviewed through a literature review one of the latest promising approach, the triad approach, in order to understand its area of application in ecosystems, the ways of applicability and effective actual application. In the case of diffuse pollution, where all the criteria of the Triad approach can differ in their conclusion for the risk, we showed that some particularities had to be added or better used either in the chemical, ecological or ecotoxicological approaches to be able to clearly identify the risk and to address the uncertainties linked to the low, sublethal contents of contaminants.